A prospective comparison of telemedicine versus in-person delivery of an interprofessional education program for adults with inflammatory arthritis. (February 2017) - Kennedy, Carol A; Warmington, Kelly; Flewelling, Carol; Shupak, Rachel; Papachristos, Angelo; Jones, Caroline; Linton, Denise; Beaton, Dorcas E; Lineker, Sydney; Hogg-Johnson, Sheilah
Introduction: We evaluated two modes of delivery of an inflammatory arthritis education program ("Prescription for Education" (RxEd)) in improving arthritis self-efficacy and other secondary outcomes. Methods: We used a non-randomized, pre-post design to compare videoconferencing (R, remote using telemedicine) versus local (I, in-person) delivery of the program. Data were collected at baseline (T1 ), immediately following RxEd (T2 ), and at six months (T3 ). Self-report questionnaires served as the data collection tool. Measures included demographics, disorder-related, Arthritis Self-Efficacy Scale (SE), previous knowledge (Arthritis Community Research and Evaluation Unit (ACREU) rheumatoid arthritis knowledge questionnaire), coping efficacy, Illness Intrusiveness, and Effective Consumer Scale. Analysis included: baseline comparisons and longitudinal trends (R vs I groups); direct between-group comparisons; and Generalized Estimating Equations (GEE) analysis. Results: A total of 123 persons attended the program (I: n  = 36; R: n  = 87) and 111 completed the baseline questionnaire (T1 ), with follow-up completed by 95% ( n  = 117) at T2 and 62% ( n  = 76) at T3 . No significant baseline differences were found across patient characteristics and outcome measures. Both groups (R and I) showed immediate effect (improved arthritis SE, mean change (95% confidence interval (CI)): R 1.07 (0.67, 1.48); I 1.48 (0.74, 2.23)) after the program that diminished over six months (mean change (95% CI): R 0.45 (−0.1, 0.1); I 0.73 (−0.25, 1.7)). For each of the secondary outcomes, both groups showed similar trends for improvement (mean change scores (95% CI)) over time. GEE analysis did not show any meaningful differences between groups (R vs I) over time. Discussion: Improvements in arthritis self-efficacy and secondary outcomes displayed similar trends for I and R participant groups.